Answer: 1 and 4 are correct
Step-by-step explanation: good luck!
Answer:
-18
Step-by-step explanation:
you add 12 and six together and you get 18. Then you put a negative sign in front of it
Answer:
y = -5x - 10
Step-by-step explanation:
-8-2 -10
____ = ___ = -5
3 - 1 2
Answer:
The answer is choice 3.
Step-by-step explanation:
I've had this equation b4
First, you'll use the "Log power rule," which says that
![\log_ax^p=p\log_ax](https://tex.z-dn.net/?f=%5Clog_ax%5Ep%3Dp%5Clog_ax)
. In this case, you're going from the form on the right (with p in front of the log) to the form on the left (with p in the exponent position). So, the expression becomes:
![\log_7x^4+\log_7y^8+\log_7z^4](https://tex.z-dn.net/?f=%5Clog_7x%5E4%2B%5Clog_7y%5E8%2B%5Clog_7z%5E4)
Then, you'll use the "Log product rule," which says that
![\log_a(xy)=\log_ax+\log_ay](https://tex.z-dn.net/?f=%5Clog_a%28xy%29%3D%5Clog_ax%2B%5Clog_ay)
. Again, you're going from the form on the right to the form on the left (basically, from the sum of the logs, to a log of the products). So you get:
![\log_7(x^4y^8z^4)](https://tex.z-dn.net/?f=%5Clog_7%28x%5E4y%5E8z%5E4%29)
There's your expression simplified into a simple logarithm.